Fluctuation in Blood Pressure and Intraocular Pressure in Normal Tension Glaucoma Using Ambulatory Monitoring. Issue 4 (April 2021) - Tan, Boo Hui; Young, Alexandra; Bianchi, Eleonora; Brown, Lyndsay; Tatham, Andrew J.
Abstract : Précis: Ambulatory blood pressure (BP) and intraocular pressure (IOP) monitoring of patients with normal tension glaucoma (NTG) revealed features of vascular dysregulation including hypertension, blunted nocturnal BP dipping, and morning BP surge. Purpose: The aim was to examine ambulatory fluctuations in IOP and BP in patients with NTG. Methods: A prospective study of 45 participants with NTG and 10 controls. All participants had a comprehensive ophthalmological examination followed by glaucoma medication washout. Patients using systemic antihypertensives were excluded. IOP and BP were recorded using home monitoring over 48 hours using a self-rebound tonometer and ambulatory blood pressure monitor. BP was recorded every 30 minutes by day and every 60 minutes overnight. IOP was recorded at 09:00, 11:00, 13:00, 16:00, 20:00, and 04:00. Results: Participants with NTG had a median mean deviation (MD) of −4.66 dB (interquartile range: −7.16 to −2.81 dB) in the worse eye. Among those with glaucoma, 18 of 45 (40%) had normal nocturnal BP dipping, 24 (53%) blunted dipping and 3 (6.7%) exaggerated dipping. Each 10 mm Hg lower minimum sleeping systolic BP was associated with a 0.9 dB (95% confidence interval: 0.1-1.6 dB) worse MD. Sixteen of 45 participants with glaucoma (35.6%) and 1 of 10 controls (10%) were found to have systemic hypertension on ambulatory blood pressure monitoring and 32 of those with glaucoma (71%) had a surge in morning BP, compared with 5 controls (50%). There was no difference in MD between patients with normal, exaggerated and blunted dipping ( P =0.813). Conclusions: Though glaucoma has been associated with exaggerated nocturnal BP dipping, we found a higher proportion of patients had systemic hypertension, blunted nocturnal BP dipping, and a morning BP surge, measures also associated with vascular dysregulation. Abstract : Supplemental Digital Content is available in the text.